From Formation to Evaluation: Optimising groupwork in STEM Degree Apprenticeships (UK and Ireland Engineering Education Research Network Conference Proceedings 2023, 2024)
Engineering degree apprenticeships provide three to six years of job opportunities and training that lead to university qualifications up to and equivalent of a postgraduate degree. Within an apprentice’s time in higher education (HE), many are required to complete groupwork projects which bring several benefits and some challenges. This paper explores the effects and limitations of group work in the context of degree apprenticeships whilst discussing a plethora of group selection and assessment method solutions. This includes student self-selection methods in comparison to teacher-selected and randomisation for group selection; a suitable method of selection should be unbiased and optimise advantages of collaborative working. Through understanding the most effective form of assessment for apprentices, an academic policy can be adapted and influenced – acknowledging the learning differences between undergraduate students and degree apprentices. As part of this work, a comprehensive literature review was carried and a survey was conducted and completed by the Bsc Digital and Technology Solutions students, BEng Applied Professional Engineering Programme students among others at the University of Warwick. The results of the survey provided quantitative and qualitative data surrounding group work. Furthermore, the paper suggests appropriate solutions to group work issues surrounding the effectiveness of group work for degree apprentices, optimal group selection-methods, group performance, ensuring equal contributions and assessment and grading methods. The paper addresses some of the problems encountered by apprentices during their studies such as the free-rider problem and unequal division of work - providing solutions towards minimising such problems, including the integration of web-based tools such as MS Planner.